ESG Disclosure and Employee Turnover. New Evidence from Listed European Companies - Garsaa, Aziza; Paulet, Elisabeth (Relations industrielles / Industrial Relations, 2022)
SummaryWe explored how company transparency, as measured by ESG (Environmental, Social and Governance) disclosure, affected the employee turnover of 212 multinational corporations that were listed in the European capital market during the 2010-2017 period. We also examined the role of the business environment by looking at the company’s ESG reporting system and its economic sector. To analyze how ESG disclosure affected employee turnover at any point of its conditional distribution, we used a panel data quantile regression model. ESG disclosure was found to be negatively associated with employee turnover. Employee turnover, as well as the extent to which it is affected by ESG disclosure, was found to depend strongly on the conditional distribution of the turnover rate, the sector and whether ESG disclosure is mandatory or voluntary. Our findings were confirmed by a robustness check analysis. In conclusion, the relationship between company transparency and employee turnover depends strongly on the institutional context and, especially, on disclosure regulation. The more a company is scrutinized, the more it will try to be socially responsible to maintain and/or improve its reputation and thus reassure and satisfy its stakeholders. AbstractWe sought to analyze the relationship between ESG (Environmental, Social and Governance) disclosure and employee turnover. We also examined how this relationship is affected by regulation of ESG reporting and by sector characteristics. A panel data quantile regression model was applied to data from 212 multinational corporations that were listed in the European capital market during the 2010-2017 period. ESG disclosure was found to be negatively associated with employee turnover. Employee turnover, as well as the extent to which it is affected by ESG disclosure, was found to depend strongly on the conditional distribution of the turnover rate, the economic sector, and whether ESG disclosure is mandatory or voluntary. A robustness check clearly confirmed our findings.